(untitled) - Curtis, Gerald L. (New York, 1999)
The Logic of Japanese Politics offers a hugely fascinating tour through contemporary Japanese politics. Gerry Curtis makes the mysterious understandable while shaking up your view of what might have seemed obvious. Specialists will appreciate Curtis expertise, but anyone who loves politics will be grateful for this insightful look at how power works in Japan.
Keywords: Political culture; Japan